2017
DOI: 10.20965/jaciii.2017.p0031
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Data Mining Techniques and Applications

Abstract: Data mining is the analytics and knowledge discovery process of analyzing large volumes of data from various sources and transforming the data into useful information. Various disciplines have contributed to its development and is becoming increasingly important in the scientific and industrial world. This article presents a review of data mining techniques and applications from 1996 to 2016. Techniques are divided into two main categories: predictive methods and descriptive methods. Due to the huge number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…It consists in applying statistical and artificial intelligence (AI) methods to model large data sets (Gorunescu, 2011). More precisely, DM aims at providing prediction and/or description of the data (Pruengkarn et al, 2017). On the basis of the available data, the first aim is to predict which are the more plausible values of some variables; the second aim is to search for characteristics and patterns to describe the data.…”
Section: Introductionmentioning
confidence: 99%
“…It consists in applying statistical and artificial intelligence (AI) methods to model large data sets (Gorunescu, 2011). More precisely, DM aims at providing prediction and/or description of the data (Pruengkarn et al, 2017). On the basis of the available data, the first aim is to predict which are the more plausible values of some variables; the second aim is to search for characteristics and patterns to describe the data.…”
Section: Introductionmentioning
confidence: 99%
“…The use of data mining so far is commonly used to obtain optimal information from a large group of large databases that have complexity [5]. In a study of single Pap smear image classification found in the Herlev dataset [4], data mining was used to get information from 20 features in the data to identify pathologic cases of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, when data are gathered at inconsistent intervals, the model must be adjusted accordingly. While this review does not delve into time-series pre-processing, the research by Pruengkarn et al [138] can be used as a resource for a thorough understanding of the matter.…”
mentioning
confidence: 99%